Vital roles of nano silica in synthetic based mud for high temperature drilling operation - Yusof, M.A.M. (American Institute of Physics Inc., 2015)
At high temperature drilling, chemicals degradation occurs which reduce the effectiveness of the drilling fluid. There is a potential that by using nano sized particles which have thermal stability up to 2500Â°F to be used as a stabilizer to withstand the harsh condition. Therefore, this project aims to identify the performance of synthetic-based mud (SBM) with nano silica for high temperature drilling operation. A conventional SBM performance has been compared with additional percentages of nano silica. 20 and 40 of nano silica out of fluid loss weight has been added into the SBM and analyzed the rheological properties and other drilling fluid properties. The conventional SBM formulation has lost some amount of weighting material or solids in the mud and has been replaced by lighter and smaller size of nanoparticles. It has reduced the rheological properties of the mud but the gelation formed by nano silica material has given higher gel strength. Also, nano silica potentially plugs the porous media, resulted in lower filtration loss measurement and thinner mud cake ranged 20 to 50 respectively. Â© 2015 AIP Publishing LLC.